2020
DOI: 10.3390/foods9060713
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant and Enzyme Inhibitory Properties of Different Extracts Obtained from Spent Coffee Ground and Coffee Silverskin

Abstract: In a world where an eco-friendlier approach is becoming more and more necessary, it is essential to reduce waste production and to reuse residues of the company’s supply chain. Coffee silverskin (CS) and spent coffee ground (SCG), two by-products of coffee production, are important sources of bioactive compounds and, for this, some authors have proposed their reuse in the nutraceutical, food, and cosmetic sector. However, their potential enzyme inhibitory properties have been poorly investigated. Hence, the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 60 publications
6
50
2
1
Order By: Relevance
“…Therefore, the solvent type significantly influenced the analyte extraction, and the EtOH : H 2 O and MeOH : H 2 O were shown to be the most efficient. Similar outcomes were reported in another recent work [ 21 ] which dealt with the chemical composition and some biological properties of different SCG and coffee silverskin (CS) extracts. Caffeine (41047.71-52346.41 ± 1896.25-2536.98 μ g g −1 ) and 5- O -caffeoylquinic acid (5-CQA) (7569.25-13256.35 ± 305.21-499.74 μ g g −1 ) were the most abundant in all extracts followed by chlorogenic acids, i.e., 3- O -caffeoylquinic acid (3-CQA) (2324.33-4317.31 ± 100.89-185.42 μ g g −1 ) and 3,5- O -dicaffeoylquinic acid (3,5-diCQA) (902.34-1325.98 ± 58.12-88.23 μ g g −1 ).…”
Section: Resultssupporting
confidence: 87%
“…Therefore, the solvent type significantly influenced the analyte extraction, and the EtOH : H 2 O and MeOH : H 2 O were shown to be the most efficient. Similar outcomes were reported in another recent work [ 21 ] which dealt with the chemical composition and some biological properties of different SCG and coffee silverskin (CS) extracts. Caffeine (41047.71-52346.41 ± 1896.25-2536.98 μ g g −1 ) and 5- O -caffeoylquinic acid (5-CQA) (7569.25-13256.35 ± 305.21-499.74 μ g g −1 ) were the most abundant in all extracts followed by chlorogenic acids, i.e., 3- O -caffeoylquinic acid (3-CQA) (2324.33-4317.31 ± 100.89-185.42 μ g g −1 ) and 3,5- O -dicaffeoylquinic acid (3,5-diCQA) (902.34-1325.98 ± 58.12-88.23 μ g g −1 ).…”
Section: Resultssupporting
confidence: 87%
“…Several studies showed the great potential of different plant by-products to be reconsidered as an important and cheaper source of ADFs and not as a waste. Thus, the apple pomace and peel [ 47 ], red grape pomace [ 48 ], cabbage powder [ 49 ], mango peel powder [ 50 ], guava peel [ 51 ], blueberry pomace powder [ 52 ], cocoa bean shell [ 53 ], pineapple pomace [ 54 ], coffee husk [ 55 ] and spent coffee grounds [ 56 , 57 ], are reported as sources with a high content of dietary fibers and antioxidant compounds. Table 3 summarizes the main advantages of the addition of ADFs to different meat products.…”
Section: Nutritional Enrichmentmentioning
confidence: 99%
“…It is a source of minerals such as potassium (21,100 mg/kg dry basis (db)), iron (843 mg/kg db), sodium (57 mg/kg db), manganese (50 mg/kg db) and zinc (22 mg/kg db), among others [9]. The enzyme inhibitory properties of CS extracts and peptide composition of CS protein hydrolysates have been investigated, from the perspective of their application in the pharmaceutical and nutraceutical industry [24,25]. The holistic concept of food production tries to connect differing goals, such as the highest product quality and safety, highest production efficiency and the integration of environmental aspects into product development and food production.…”
Section: Introductionmentioning
confidence: 99%
“…CS has been reported as a source of chlorogenic acids; however, to date, there are few reports concerning the content of 5CQA in CS, and those that exist show controversial results, since the reported concentrations are in the range of 1000 to 11,678 mg of 5CQA/kg of CS [ 11 , 18 , 19 , 20 ]. Different studies have shown the functional properties of CS such as a high dietary fiber content (54.11 to 74.15 g/100 g of CS) [ 9 , 21 , 22 ] and a total phenolic content in the range of 4.6 to 46.65 mg/g, depending on the extraction method employed [ 11 , 21 , 23 , 24 ]. The principal constituents of its fibrous tissues are cellulose (24%) and hemicellulose (17%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation